The joint effect of feedback order and reward schemes on prevalence-induced perceptual decisions - Hanshu Zhang; Jun Zheng; Yun-Yen Tsai; Cheng-Ta Yang (Scientific Reports)
Abstract Both target prevalence and associated rewards can bias perceptual decisions. Prior studies have shown that shifts in target prevalence can alter decision criteria, and that feedback can further modulate these effects. The present study aims to investigate whether reward schemes similarly interact with feedback to shape perceptual decision biases. In Experiment 1, participants were assigned a categorization task with or without trial-by-trial feedback, and targets in low- and regular-prevalence conditions yielded the same expected value. The impact of the reward scheme was further investigated in Experiment 2 by introducing severe penalties for misses. Contrary to our expectations, the results suggested that reward schemes had minimal effects in both experiments. Importantly, the sequence in which feedback was given proved crucial. The participants who initially did not receive feedback made more liberal decisions than did those who first received feedback but later had it removed. These findings offer valuable insights for optimizing performance across varying target prevalence scenarios in future research.